Three-dimensional finite element modeling and theoretical analysis of concrete confined with FRP rings. (1st May 2021) - Zeng, Jun-Jie; Chen, Shu-Peng; Zhuge, Yan; Gao, Wan-Yang; Duan, Zhi-Jian; Guo, Yong-Chang
Highlights: The arching action behavior between two adjacent FRP rings/ties is investigated using an advanced FE approach. Numerical results demonstrate that the presence of the arching action assumption. The shape of the arch is influenced primarily by the FRP ring clear spacing. A theoretical model for the axial stress distribution in the middle of two adjacent FRP rings/ties is proposed. A new confinement effectiveness ratio is proposed and verified by test results. Abstract: The confinement mechanism of concrete fully confined with fiber-reinforced polymer (FRP) jacket (FRP jacketed concrete) is different from that of concrete partially confined with FRP (i.e., FRP ring-confined concrete and FRP tie-confined concrete) in that the confinement in the latter is non-uniform along the longitudinal direction. In order to build a bridge between FRP jacketed concrete and FRP ring/tie-confined concrete, the current design of concrete confined with FRP rings/ties relies on the "arching action" assumption, which is not necessarily accurate as it was proposed for concrete confined with steel stirrups. Moreover, the arching action assumption usually adopts a hypothesis that the arching action angle equals to 45°, which has not been verified by any theoretical or experimental evidence. To this end, a revised analysis model has been implemented in an advanced finite element (FE) approach to study the axial stress distributions in concrete confined with FRP rings. The stress distribution at the center level of two adjacent FRP rings/ties is obtained, and the relationship between the arching action angle and controlling parameters (i.e., unconfined concrete strength, FRP width, FRP thickness and clear spacing of FRP rings) is established based on a proposed theoretical model of arching action angle. A new confinement effectiveness coefficient is then proposed, leading to a much more reliable prediction of the FRP ring-confined concrete in circular columns. The results presented in the current study can be easily extended to the concrete columns internally reinforced with FRP ties/spiral.